SETTLEMENT AS A TOURISM ATTRACTIONS Case Study : Banjar Karang Dalem I Settlement, Desa Bongkasa Pertiwi, Badung Regency, Bali-Indonesia - Prabawa, Made Suryanatha; Gunawarman, Anak Agung Gede Raka (Journal of Architectural Research and Education, 2020)
Tourism Village is related to Community-Based Tourism (CBT) where all management and development includes the participation of local communities. Badung Regency launched 11 Badung Tourism Villages through Perbup no. 47 of 2010. 1 of 11 Tourism Villages that are declared is Bongkasa Pertiwi Village. In Perbup it is very clear that Br. Karang Dalem I, the residents and their settlements should become icons of village tourism. The issue that was caught in the field was that embedding it as a tourist village did not have a positive impact on the settlement at Br. Karang Dalem I, Bongkasa Pertiwi Village, where some of its residents are pursuing a unique profession, namely traditional silver craftsmen. The craftsman profession, which used to be the majority, now only has 8 residents working (previously almost every household) and none of them are young. This issue is the basis for the need to conduct further studies to find the tourism potential of the Br. Karang Dalem I as a settlement for silversmiths in line with Bongkasa Pertiwi Village as a Tourism Village. The purpose of this study was to explore, collect data, analyze the spatial aspects of the settlement of Br. Karang Dalem I which is somewhat unique (Typical / Traditional) with an understanding of the meaning behind the existence of this spatial aspect, because initial observations of several settlements still maintain their traditional architectural form. This research is supported by an understanding of the concept of a tourism village, tourism architecture as a core, Balinese traditional settlements, and a study on the development of the tourism village of Bongkasa Pertiwi as previous research. This study will use an exploratory-qualitative method with cross-examination data analysis to obtain the best research conclusions.This research findings shows that architectural components of Banjar Karang Dalem I settlement are classified as special tourism interest (WMK). The Data show that 6 (six) aspects of sepcial tourism interest are found in Banjar Karang Dalem I settlement such as Settlement Layout Pattern,Â TelajakanÂ Garden, The use of Kori as entrance gate, House using â€œNatahâ€ As Arrangement Pattern, etc.Â